ANALISIS SISTEM DAN PROSEDUR PELAPORAN SURAT PERTANGGUNGJAWABAN (SPJ) PADAUNIT PENGEMBANGAN PRODUKTIVITAS DAERAH DINAS TENAGA KERJA DAN TRANSMIGRASI PROVINSI KALIMANTAN BARAT - B51109075, Poniman Muklis (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2013)
Problems on Regional Productivity Development Unit of West Kalimantan Province is about SPJ late reporting of a predetermined limit Affairs Minister Decree No. 21 of 2011yaitu later than December 10 and the delivery letter Accountability (SPJ) is less than 75% of the Fund Disbursement Order (SP2D) were published, so that makes the writer interested to analyze the effectiveness and keefesienan SPJ Reporting process. The purpose of this study was to determine the extent to which the effectiveness and keefesienan and factors - factors that influence according to Ministry Decree No. ineffectiveness. 73 / PMK/.05 / 2008 and efficiency by Permendagri No. 21 of 2011 on the systems and procedures SPJ Reporting on Regional Productivity Development Unit (UP2D). The research method used is Diskriptif, the data collection techniques are direct observation, interviews, Study Library, Study Documentary. While analysis tools used are effectiveness, efficiency, and Evaluation Flow Chart Interview. Based on the results of the analysis can be seen that the reporting has not been fully implemented SPJ UP2D Effective and Efficient, this is caused by factors - factors that limit the non-compliance reporting, the lack of legal basis for the delay in reporting SPJ sanctions, DPA Submission Process - SKPDs not timely and number of completeness that must be met and authorized both the Internal and External. Keywords: Effective, Effectiveness, Systems and Procedures